The big bang theory. The complete ninth season [videorecording (DVD)] - Galecki, Johnny; Parsons, Jim, 1973-; Cuoco, Kaley; Helberg, Simon
Prepare to enter phase nine of television's perpetual laughter experiment as the show successfully fuses the elements of science and sitcom. Our two genius roommates, Leonard and Sheldon, and their friends are back once again (smarter, but no wiser). Last season, Sheldon went soul-searching (on a train, of course) and was prepared to make some substantial revisions on his Relationship Agreement with Amy, when everything changed.